GAMBARAN FAKTOR YANG BERHUBUNGAN DENGAN PENDERITA KUSTA DI KECAMATAN TAMALATE KOTA MAKASSAR - Manyullei, Syamsuar; Utama, Deddy Alif; Birawida, Agus Bintara (ARCHIVE OF COMMUNITY HEALTH, 2012)
Leprosy is an infectious disease caused by Mycobacterium leprae. Based on data from Pemerintah Kota Makassar (2007), Tamalate sub district is an area in which new cases detection are quite high every year (Makassar as many as 15 cases per year). This research aims to explore the factors associated with lepers in the Tamalate District of Makassar. Determinants of lepers are knowledge, age, gender, physical contact and personal hygiene. This research is driven by observational study with descriptive approach. Study population includes all lepers living in Tamalate District and registered since January 2008 - December 2011 from four health centers in the district. The sample is lepers currently on treatment or have completed treatment (RFT) aged ? 15 years. Thus, sampling method uses exhaustive sampling with a sample size of 51 people and the data are analysed with univariate dan bivariate analysis. These results indicate that, 66.7% lepers have su?  cient knowledge about leprosy, 78.4% lepers were 15 years old or older when they began to be diagnosed as lepers, 60.8% lepers are male, 84.3% lepers are at high risk of infected leprosy regarding to physical contact, and 49% lepers have good personal hygiene. Lepers have su?  cient of knowledge about leprosy, lepers were 15 years old or older when they began to be diagnosed as lepers. Most of lepers are male, lepers have good personal hygiene. Thus, this research recommends to increase health promotion on leprosy, minimize physical contact with lepers, and improve personal hygiene such as maintaining to wash hands.
Keywords: Lepers, Knowledge, Physical Contact, Personal Hygiene